2015
DOI: 10.4269/ajtmh.15-0168
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of Monkeypox into a Community and Household: Risk Factors and Zoonotic Reservoirs in the Democratic Republic of the Congo

Abstract: Abstract. An increased incidence of monkeypox (MPX) infections in the Democratic Republic of the Congo was noted by the regional surveillance system in October 2013. Little information exists regarding how MPX is introduced into the community and the factors associated with transmission within the household. Sixty-eight wild animals were collected and tested for Orthopoxvirus. Two of three rope squirrels (Funisciurus sp.) were positive for antibodies to Orthopoxviruses; however, no increased risk was associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
184
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(194 citation statements)
references
References 17 publications
1
184
0
9
Order By: Relevance
“…To date human cases of monkeypox have been reported from ten African countries -Democratic Republic of the Congo, Republic of the Congo, Cameroon, Central African Republic, Nigeria, Ivory Coast, Liberia, Sierra Leone, Gabon and South Sudan (WHO, 2018a,b). Whilst the cessation of smallpox vaccination might be an important risk factor, there may be other factors which could explain the increase (Nolen et al, 2015;Sklenovská and Van Ranst, 2017) such as: (a) higher frequency of contact with animal host reservoirs by children and young adults, (b) deforestation leading to increased exposure of humans with displaced animals, (c) Wars, conflicts and poverty leading to population movement into forests, (d) reliance on rodents for food, (e) increased population density, and (f) Improved surveillance and diagnostic capability, although the latter was probably not the case due to reduced resources. Further multidisciplinary, regional collaborative research, including carefully designed case-control and cohort studies are required to fill the major knowledge gaps in the epidemiology, host reservoir, transmission, pathogenesis surveillance and prevention, as well as to explore potential prevention, infection control and treatment interventions.…”
Section: Monkeypox In Central and West Africamentioning
confidence: 99%
“…To date human cases of monkeypox have been reported from ten African countries -Democratic Republic of the Congo, Republic of the Congo, Cameroon, Central African Republic, Nigeria, Ivory Coast, Liberia, Sierra Leone, Gabon and South Sudan (WHO, 2018a,b). Whilst the cessation of smallpox vaccination might be an important risk factor, there may be other factors which could explain the increase (Nolen et al, 2015;Sklenovská and Van Ranst, 2017) such as: (a) higher frequency of contact with animal host reservoirs by children and young adults, (b) deforestation leading to increased exposure of humans with displaced animals, (c) Wars, conflicts and poverty leading to population movement into forests, (d) reliance on rodents for food, (e) increased population density, and (f) Improved surveillance and diagnostic capability, although the latter was probably not the case due to reduced resources. Further multidisciplinary, regional collaborative research, including carefully designed case-control and cohort studies are required to fill the major knowledge gaps in the epidemiology, host reservoir, transmission, pathogenesis surveillance and prevention, as well as to explore potential prevention, infection control and treatment interventions.…”
Section: Monkeypox In Central and West Africamentioning
confidence: 99%
“…Today, entire households are mostly or completely susceptible, allowing significant potential for an additional human-to-human transmission. During the 2013 outbreak in DRC, frequent transmission was documented within households [3,7] with a median attack rate of 50% [7]. A recent study [7] observed that the group most often affected is school-aged boys.…”
Section: Why Is the Disease Emerging In Drc?mentioning
confidence: 99%
“…During the 2013 outbreak in DRC, frequent transmission was documented within households [3,7] with a median attack rate of 50% [7]. A recent study [7] observed that the group most often affected is school-aged boys. Risk factors for transmission included sharing a bed or room and using the same utensils with an infected patient.…”
Section: Why Is the Disease Emerging In Drc?mentioning
confidence: 99%
See 2 more Smart Citations